PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi pada Perusahaan Industri Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Sheila Nurfitriana Sasmita (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine the effect of good corporate governance towards the company performance of property & real estate industry firms listed in Indonesia Stock Exchange during 2012-2016. The corporate governance measured by managerial ownership, institutional ownership and proportion of independent board commissioners, while corporate performance proxied by Tobin’s Q ratio. The population in this research is all  company in property & real estate industry listed in Indonesia Stock Exchange for the years 2012-2016. Purposive sampling method was used to collect the data from 9 sample companies. The results show that managerial ownership has negative and insignificant effect on company performance, institutional ownership has a negative and significant effect on company performance, and the proportion of independent board of commissioners has a positive and significant effect on company performance.Keywords: Good Corporate Governance, Managerial Ownership, Institutional Ownership, Proportion of Independent Board of Commissioners, Corporate Performance, Tobin's Q